Efektivitas Pelayanan Transportasi Umum BisKita TransPakuan di Kota Bogor - Ardityo Rahardjo; Teguh Yuwono (Journal of Politic and Government Studies, 2026)
Public transportation is a vital element in supporting inclusive and sustainable urban mobility. The transfer of BisKita TransPakuan’s management to the Bogor City Transportation Agency raises fundamental questions about the extent to which this service effectively meets the needs of its users. This study aims to analyze the effectiveness of BisKita TransPakuan’s public transportation management in Bogor City following the management transition, as well as to identify factors influencing user satisfaction and intention to use the service. This study employs a mixed method approach integrating qualitative and quantitative methods, grounded in Public Service Theory and the Citizen-Centric Governance framework. Data were collected through in-depth interviews, field observations, questionnaires distributed to 100 users, and documentation studies. Quantitative 1 analysis was conducted using Partial Least Squares – Structural Equation Modeling (PLS-SEM). Qualitative findings indicate that the dimensions of efficiency and community participation were considered sufficiently effective, whereas equality and accessibility, responsiveness, and technology utilization remained suboptimal. This is reflected in bus stops that are not yet fully disability-friendly, low user awareness of complaint channels—with 33% unaware of their existence and 38% feeling their complaints were not followed up—as well as limited public familiarity with the BisKita application. The customer satisfaction index was recorded at 4.21. PLS-SEM results reveal that equality and accessibility, along with community participation, significantly influence user satisfaction. Technology utilization was found to affect both efficiency perception and user satisfaction, while responsiveness showed no significant influence. The strongest mediation path was identified through technology utilization, which affects user satisfaction and subsequently impacts Intention to Use. The management of BisKita TransPakuan demonstrates meaningful progress, yet remains not fully effective. This study recommends bus stop renovations to improve accessibility, intensified socialization of the BisKita application, strengthened transparent complaint follow-up mechanisms, fleet expansion, and the accelerated activation of Corridors 3 and 4 to realize an inclusive, responsive, and sustainable public transportation system in Bogor City.